2020
DOI: 10.3390/ma13214704
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Hamburg Wheel-Tracking Device Stripping Performance Properties of Recycled Hot-Mix Asphalt Mixtures

Abstract: Moisture damage in hot mix asphalt pavements is a periodic but persistent problem nowadays, even though laboratory testing is performed to identify different moisture-susceptible mixtures. In this study, a Hamburg Wheel Tracking device (HWTD) was used for rutting tests which were conducted on control and a high percentage of recycled asphalt pavement (RAP), i.e., 30%, 50% and 100% of virgin mixtures, under air dry and water-immersed conditions. Similarly, the extracted bitumen from RAP was tested for binder ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
(39 reference statements)
2
5
0
Order By: Relevance
“…Aligned with prior research [59,60], the HWT test outcomes substantiate the critical role of NMAS in the rutting resistance of SMA mixtures for BRT systems. The study's results echo the findings of previous research, indicating that the 13 mm NMAS mixture, incorporating 4% WPA, 25% RAP, and the optimized binder, outperforms its 10 mm NMAS counterpart.…”
Section: Hamburg Wheel Tracking Testsupporting
confidence: 62%
“…Aligned with prior research [59,60], the HWT test outcomes substantiate the critical role of NMAS in the rutting resistance of SMA mixtures for BRT systems. The study's results echo the findings of previous research, indicating that the 13 mm NMAS mixture, incorporating 4% WPA, 25% RAP, and the optimized binder, outperforms its 10 mm NMAS counterpart.…”
Section: Hamburg Wheel Tracking Testsupporting
confidence: 62%
“…In general, the State Transportation Authority of the United States stipulates the use of an asphalt mixture that loads 20,000 cycles. Moreover, stripping should occur after at least 10,000 cycles and does not exceed 20 mm of settling at the end of the cycles [25,31]. In both asphalt mixture types, it was found that the settlement did not exceed 20 mm after 20,000 cycles.…”
Section: General Analysismentioning
confidence: 90%
“…In South Korea, it is specified to use rejuvenators when reclaimed aggregates used in an asphalt mix design exceed 25% [19]. Since the common practice incorporates about 30% reclaimed aggregates, the use of rejuvenators has become orthodox [19,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of strength in HMA occurs when the bond between binder and aggregate is weakened. Stripping begins at the bottom of the HMA layer and travels upward [ 12 , 13 ], leading to a gradual loss of strength over the years and the promotion of rutting and shoving in the wheel path [ 14 ]. Additionally, the adhesive bonding at the aggregate–binder interface is more likely to be affected by water than the cohesive failure in the binder [ 15 ].…”
Section: Introductionmentioning
confidence: 99%